Calculation of heavy oil viscosity based on an Arrhenius model. (18th June 2017) - Liu, Yonghui; Shi, Shuqiang; Wang, Yongqing; Feng, Yibo; Luo, Chengcheng
ABSTRACT: The commonly used heavy oil viscosity models are considered as the function of temperature, API, and colloid asphalt. Some of the published correlations are just for one oil field or a region, but they have some limitations when the viscosity of other oil samples is calculated. Even these multi-parameter models cannot be used in the absence of API or colloid asphalt content data. This paper presents a new and simple method to predict the viscosity of heavy oil based on the Arrhenius model, which only needs to measure the viscosity of heavy oil under the temperature condition of 50°C. This method can predict the viscosity in the absence of API or colloid asphalt content data. A total of 31 heavy oil samples were collected from published literature works to test the accuracy and reliability of the new method and other eight classical models. The new method can predict the viscosity with an average relative error of 2.37% and an average absolute error of 8.43%. Compared with the commonly used model, the new method shows consistently accurate results. It also reduces the experimental workload and calculation process, without measuring the API and asphalt content data.